The Internet in Cyprus 2010, Final Report - Gialamas, Vassilis; Milioni, Dimitra L.; Tsapatsoulis, Nicolas; Kyza, Eleni A.; Lambrinos, Lambros; Demertzis, Nicolas; Kyriakides, Christopher; Panos, Dionysis (Cyprus University of Technology, 2010)
The Cyprus World Internet Project survey was conducted in late 2008. A sample of 1000 Cypriots were interviewed regarding their use of and attitudes to the Internet.
Keywords: Internet--Cyprus; Internet--Moral and ethical aspects; Internet--Political aspects; Internet--Social aspects--Cyprus